2018
DOI: 10.1016/j.drugpo.2018.05.011
|View full text |Cite
|
Sign up to set email alerts
|

An altered state? Emergent changes to illicit drug markets and distribution networks in scotland

Abstract: The findings have the capacity to further inform police and practitioners about the diverse and evolving nature of drug distribution in Scotland (with a particular focus on the west of the country), so that they may become more effective in improving the safety and wellbeing of people, places and communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…It is recognised, often via (auto) biographical accounts, that those SOCGs who initially became involved in the emerging drugs trade during the last quarter of the 20th Century were comprised of professional criminals who previously robbed jewellers and banks. This shift in criminal speciality occurred for several reasons, including globalisation (Pitts 2008), free market policies (Pearson and Hobbs 2001), increased access to illegal drugs from overseas (Densley et al 2018) and risk mitigation owing to dedicated law enforcement action, technological advances, and improved security (Walsh 2011). Of course, SOCGs existed in Scotland (and elsewhere) in earlier periods as a form of class resistance (e.g., Hobsbawm 1969) and a provisional solution for alleviating strain (Cohen 1955).…”
Section: Socg and Robberymentioning
confidence: 99%
“…It is recognised, often via (auto) biographical accounts, that those SOCGs who initially became involved in the emerging drugs trade during the last quarter of the 20th Century were comprised of professional criminals who previously robbed jewellers and banks. This shift in criminal speciality occurred for several reasons, including globalisation (Pitts 2008), free market policies (Pearson and Hobbs 2001), increased access to illegal drugs from overseas (Densley et al 2018) and risk mitigation owing to dedicated law enforcement action, technological advances, and improved security (Walsh 2011). Of course, SOCGs existed in Scotland (and elsewhere) in earlier periods as a form of class resistance (e.g., Hobsbawm 1969) and a provisional solution for alleviating strain (Cohen 1955).…”
Section: Socg and Robberymentioning
confidence: 99%
“…Gangs operating 'county lines', moreover, use a single telephone number for ordering drugs, operated from outside the area, which becomes the group's 'brand'. Part of the more business focused operating model is the expansion of markets using county lines operations, which is common across London and other major UK cities, rather than being a local phenomenon (seeCoomber and Moyle 2017;Densley et al 2018; NCA 2016; Windle and Briggs 2015b). One statutory sector professional described the logic behind the targeting of new markets:The pursuit of business interests has led to greater opportunities to engage in alliances that can serve the interests of both parties.…”
mentioning
confidence: 99%
“…).County lines operations, for example, are already well developed and the emerging threats arise as gangs move onto the next stage, when local gangs seek to secure markets in rural towns that already have county lines activities run by other gangs from London or other large cities. The result is likely to be escalating conflict as gangs compete for new territory(Densley et al 2018).Local professionals and young people have identified the Mali Boys as 'different' and have explained the new operating model in terms of specific features of the gang. However, pan-London professionals and other recent research studies have identified similar features, which would suggest that it is part of a wider evolution of gang activity.…”
mentioning
confidence: 99%
“…In Scotland, OC presents primarily in the form of drug supply (Densley et al . ; Scottish Government , , ). However, Police Scotland recognise that organised criminals are involved in other forms of crime and about half of all OC groups exhibit versatility in their criminal offences (Scottish Government ).…”
Section: Organised Crime In Scotlandmentioning
confidence: 99%